Development and optimisation of a novel Plasmodium falciparum Hsp90-Hop interaction assay - Wambua, Lynn (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology, 2018)
Protein-protein interactions are involved in a range of disease processes and thus have become the focus of many drug discovery programs. Widespread drug resistance to all currently used antimalarial drugs drives the search for alternative drug targets with novel mechanisms of action that offer new therapeutic options. Molecular chaperones such as heat shock proteins facilitate protein folding, play a role in protein trafficking and prevent protein misfolding in cells under stress. Heat shock protein 90 (Hsp90) is a well-studied chaperone that has been the focus of cancer drug development with moderate success. In Plasmodium falciparum (P. falciparum), heat shock proteins are thought to play a vital role in parasite survival of the physiologically diverse habitats of the parasite lifecycle and because Hsp90 is prominently expressed in P. falciparum, the chaperone is considered a potentially ideal drug target. Hsp90 function in cells is regulated by interactions with co-chaperones, which includes Heat shock protein 70-Heat shock protein 90 organising protein (Hop). As opposed to directly inhibiting Hsp90 activity, targeting Hsp90 interaction with Hop has recently been suggested as an alternative method of Hsp90 inhibition that has not been explored in P. falciparum. The aim of this research project was to demonstrate PfHsp90 and PfHop robustly interact in vitro and to facilitate high-throughput screening of PfHsp90-PfHop inhibitors by developing and optimising a novel plate capture Hsp90-Hop interaction assay. To establish the assay, the respective domains of the proteins that mediate Hsp90-Hop interaction were used (Hsp90 C- terminal domain and Hop TPR2A domain). The human Hsp90 C-terminal domain and glutathione-S-transferase (GST) coding sequences were cloned into pET-28a(+) and murine and P. falciparum TPR2A sequences into pGEX-4T-1 plasmids to enable expression of histidine-tagged and GST fusion proteins, respectively, in Escherichia coli. The P. falciparum Hsp90 C-terminal domain sequence cloned into pET-28a(+) was supplied by GenScript. The constructs were transformed into T7 Express lysYcompetent E. coli cells and subsequent small- scale expression studies showed the recombinant proteins were expressed in a soluble form allowing for subsequent protein purification. Purification of the recombinant proteins was achieved using nickel-NTA and glutathione affinity chromatography for the His-tagged (Hsp90 C-terminal domains and GST) and GST fusion proteins (TPR2A domains), respectively. The purified proteins were used to establish and optimise mammalian and P. falciparum Hsp90- Hop interaction assays on nickel-coated plates by immobilising the His-tagged C-terminal domains on the plates and detecting the binding of the GST-TPR2A domains using a colorimetric GST enzyme assay. Z'-factor values above 0.5 were observed for both assays indicating good separation between the protein interaction signals and negative control background signals, although relatively high background signals were observed for the mammalian interaction due to non-specific binding of murine TPR2A to the plate. Designed human and P. falciparum TPR peptides were observed to be effective inhibitors of the mammalian and P. falciparum interactions, demonstrating the assay's ability to respond to inhibitor compounds. Comparison of assay performance using GST assay kit reagents and lab- prepared reagents showed the assay was more efficient using lab-prepared reagents, however, lower GST signals were observed when comparing assay performance using a custom prepared Ni-NTA plate to a purchased Ni-NTA plate. The Hsp90-Hop interaction assays were also performed using an alternative assay format in which the GST-TPR2A fusion proteins were immobilised on glutathione-coated plates and binding of the His-tagged C-terminal domains detected with a nickel-horseradish peroxidase (HRP) conjugate and a colorimetric HRP substrate. The assay showed higher interaction signals for the P. falciparum proteins but comparatively low signals for the mammalian proteins. Z'-factor values for the assay were above 0.8 for both protein sets, suggesting this assay format is superior to the GST assay. However, further optimisation of this assay format is required. This study demonstrated direct binding of PfHsp90-PfHop in vitro and established a novel and robust PfHsp90-PfHop interaction assay format that can be used in future screening campaigns.
Keywords: Plasmodium falciparum; Molecular chaperones; Heat shock proteins; Protein-protein interactions; Antimalarials